2014
DOI: 10.1175/jtech-d-13-00193.1
|View full text |Cite
|
Sign up to set email alerts
|

Global Precipitation Measurement (GPM) Ground Validation (GV) Prototype in the Korean Peninsula

Abstract: Since 2009, the Korea Meteorological Administration (KMA) has participated in ground validation (GV) projects through international partnerships within the framework of the Global Precipitation Measurement (GPM) Mission. The goal of this work is to assess the reliability of ground-based measurements in the Korean Peninsula as a means for validating precipitation products retrieved from satellite microwave sensors, with an emphasis on East Asian precipitation. KMA has a well-developed operational weather servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 60 publications
2
20
0
Order By: Relevance
“…Islam et al, 2012) and checks on surface radar calibration stability in preparation for the GPM era (e.g. Kim et al, 2014). In the GPM era the aforementioned types of study, now using the DPR instead of TRMM's Precipitation Radar (PR) continue, but the VN has also directly supported verification of mission science requirements , DSD retrieval algorithms (e.g.…”
Section: Direct Gv Datasetsmentioning
confidence: 99%
“…Islam et al, 2012) and checks on surface radar calibration stability in preparation for the GPM era (e.g. Kim et al, 2014). In the GPM era the aforementioned types of study, now using the DPR instead of TRMM's Precipitation Radar (PR) continue, but the VN has also directly supported verification of mission science requirements , DSD retrieval algorithms (e.g.…”
Section: Direct Gv Datasetsmentioning
confidence: 99%
“…This is more significant in Group 2. Several studies have discovered that as a result of low BB height, large path-integrated attenuation (PIA) and strong correction, PR is likely to overestimate the convective rain rate in the Korean Peninsula and some other regions compared with ground radars [68,69]. Chen et al [70] found that due to incorrect rain type classification, overcorrection of radar signals, poor performance of the Surface Reference Technique (SRT) module, ground clutter and geometric effects, TRMM PR overestimates the frequency of moderate rain rates.…”
Section: Comparison Of Overall Precipitationmentioning
confidence: 99%
“…GPM DPR was found to underestimate precipitation rates for rates smaller than 10 mm/h and overestimate for rates above 10 mm/h by using at-launch code and synthetic data based on the TRMM PR data [71]. and some other regions compared with ground radars [68,69]. Chen et al [70] found that due to incorrect rain type classification, overcorrection of radar signals, poor performance of the Surface Reference Technique (SRT) module, ground clutter and geometric effects, TRMM PR overestimates the frequency of moderate rain rates.…”
Section: Comparison Of Overall Precipitationmentioning
confidence: 99%
“…On that basis, we collected 225, 378, and 295 TRMM overpasses for 2012, 2013, and 2014, respectively. For GPM, there were 178, 224, and 211 for 2014.…”
mentioning
confidence: 99%
“…We have to assume that the fluctuations are a cumulative result of various 10 effects that might include e.g. hardware instability, fluctuations in the refractive index of the atmosphere, dynamic changes in the atmosphere in the time interval between SR overpass and GR sweep, non-meteorological echoes, residual errors in the geometric intersection of the volume samples, and other random error components, as noted in other studies (Anagnostou et al, 2001;Kim et al, 2014;Schwaller and Morris, 2011;Wang and Wolff, 2009;Warren et al, 2017). (3) Effect of quality weighting on bias estimation: Figure 8b and c together illustrate the benefit of taking into account GR 25 data quality (i.e.…”
mentioning
confidence: 99%